Nanocellulose as sustainable biomaterials for drug delivery - Sudipta Das (KeAi Communications Co., Ltd., 2022)
Nanocellulose (NC) has lately appeared as a member of the major promising “green” materials, garnering great attentiveness due to it’s unique features. Several new materials with huge variety of biomedical uses have been developed based on the most coveted aspects of Nanocellulose, including biodegradability, sustainability, biocompatibility and their especial physicochemical properties. There are primarily three class of Nanocellulose, every one of which is maufactured in a different way and has different qualities. In the previous couple of years, scientists have concentrated on nanocellulose-based systems which are employed as drug delivery vehicles. Controlled and sustained drug release has varying potential for different applications and administration routes; in this case, nanocellulose was used as a persistent biomaterial that aided in drug delivery. There are two different forms of nanocellulose-based biomedical materials that are currently being developed. At the molecular level, they are tissue bioscaffolds for cellular growth, drug excipients for drug administration, and enzyme/protein immobilisation and recognition. On the contrary at the macroscopic level biomaterial, they are blood vascular and soft tissue substitutes, skin and bone tissue healing materials, and antibacterial materials. The prospective biomedical use of nanocellulose will also be determined by its functional alteration.